1971
DOI: 10.1002/jobm.19710110104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastruktur der stabilen L‐Formen von Escherichia coli B und W 1655 F+

Abstract: In broth cultures thp stabje L-forms of E. coli B and TV 1655 F+ grow as spherical elements with diameters of 0.05 , u up to more than 2 p. Particles below 0.3 p in diameter are probably not, able t o propagate. L-form cells, growing in agar media, are highly pleomorph.Ultrathin sections through L-form cells show that there are no ce!l wall structures. The cells are always surrounded only by the cytoplasmic membrane. Therefore, the L-forms of the two E. coli strains under study may be designa+ed as stable L-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Electron microscopical studies have shown spherical cells, lacking the typical components of the Gram‐negative envelope, e.g. flagellae and fimbriae, the OM, the murein layer, and the periplasmic space (Schuhmann & Taubeneck, 1969; Gumpert et al , 1971). The lacking envelope components account for osmotic fragility, for resistance against cell wall‐active antibiotics (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopical studies have shown spherical cells, lacking the typical components of the Gram‐negative envelope, e.g. flagellae and fimbriae, the OM, the murein layer, and the periplasmic space (Schuhmann & Taubeneck, 1969; Gumpert et al , 1971). The lacking envelope components account for osmotic fragility, for resistance against cell wall‐active antibiotics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The lacking envelope components account for osmotic fragility, for resistance against cell wall‐active antibiotics (e.g. ampicillin), for sensitivity towards inhibitors which cannot pass the OM, for resistance to coliphage infection, and for the inability of the L‐form to mobilize genetic material via conjugation (Schuhmann & Taubeneck, 1969; Gumpert et al , 1971, 2002). Growth of the L‐form is confined to complex media, indicating strict dependency on rich nutrient supply.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, however, experimental findings have shown that several other bacterial species can grow without a protecting cell wall, and these have been collectively termed ‘stable L‐forms’ [7–9]. Such L‐form mutants are also known from a Gram‐negative E. coli laboratory strain showing no outer membrane structures (strain LW1655F+ [10]), which are typical for this model bacterium [11–13]. In particular, it has remained elusive how E. coli may have been able to shut off the biosynthesis of this essential cell structure.…”
Section: Introductionmentioning
confidence: 99%